2022
DOI: 10.1002/humu.24448
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in OOEP and NLRP5 identified in infertile patients with early embryonic arrest

Abstract: The subcortical maternal complex (SCMC), composed of several maternal-effect genes, is vital for the development of oocytes and early embryos. Variants of SCMC-encoding genes (NLRP2, NLRP5, TLE6, PADI6, and KHDC3L, but not OOEP and ZBED3) are associated with human oocyte maturation dysfunction, fertilization failure, and early embryonic arrest. In this study, we enrolled 118 Chinese patients who experienced recurrent preimplantation embryonic arrest during assisted reproductive technology treatments and perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Second, PADI6 is one of the genes encoding the subcortical maternal complex (SCMC), which is necessary for oocyte maturation and early embryonic development. Therefore, the loss and mutation of PADI6 destabilizes SCMC, resulting in abnormal oocyte maturation, fertilization failure, early embryonic developmental arrest, multilocus imprinting disorder, molar pregnancy, miscarriage, and female infertility (32,(190)(191)(192)(193)(194)(195)(196)(197)(198)(199)(200)(201)(202)(203)(204)(205)(206)(207).…”
Section: The Padi Family and Reproductive Development-related Diseasesmentioning
confidence: 99%
“…Second, PADI6 is one of the genes encoding the subcortical maternal complex (SCMC), which is necessary for oocyte maturation and early embryonic development. Therefore, the loss and mutation of PADI6 destabilizes SCMC, resulting in abnormal oocyte maturation, fertilization failure, early embryonic developmental arrest, multilocus imprinting disorder, molar pregnancy, miscarriage, and female infertility (32,(190)(191)(192)(193)(194)(195)(196)(197)(198)(199)(200)(201)(202)(203)(204)(205)(206)(207).…”
Section: The Padi Family and Reproductive Development-related Diseasesmentioning
confidence: 99%
“…The OOEP gene, similar to other genes of the complex SCMC, contributes to the symmetrical division of the zygote and is involved in the activation of the zygotic genome and also in the process of reparation DNA double-strand breaks (DSBs) [ 70 ]. Biallelic variants in OOEP lead to different phenotypes, including early embryonic developmental arrest, MLID [ 17 , 71 ].…”
Section: Genes Of Scmc Componentsmentioning
confidence: 99%
“…These NLRP genes are expressed in germ cells and pre-implantation embryos, which are not functionally identical [25]. For example, NLRP5 mutations affect early embryonic development [26]. Evidence has shown that NLRP7 involves in oocyte maturation, endometrial remodelling and placental development during early pregnancy [27].…”
Section: Introductionmentioning
confidence: 99%